Pengaruh Rasio Hutang dan Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan - Anggi Putri Kusuma Wardini; Indah Lestari; Wiwin Sukiati; Tevi Leviany; Wuri Handayani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to examine the effect of leverage, measured by the Debt to Asset Ratio (DAR), and firm size on financial performance, proxied by Return on Assets (ROA). The research applies a quantitative method with secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The population consists of 29 construction sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Using purposive sampling, 10 companies that met the research criteria were selected. Data were analyzed using multiple linear regression with the aid of EViews 12 software. The findings reveal that, partially, leverage (DAR) has no effect on financial performance, whereas firm size has a significant effect. Simultaneously, leverage and firm size significantly influence financial performance by 85%. These results highlight that firm size plays a crucial role in improving profitability, while the impact of leverage requires further contextual consideration.